For` r = tan^2(3 - theta^3)` the derivative `(dr)/(d theta)` has to be determined. Use the chain rule.

`(dr)/(d theta)` = `2*tan(3 - theta^3)*sec^2(3 - theta^3)*(-3*theta^2)`

=> `-6*theta^2*tan(3 - theta^3)*sec^2(3 - theta^3)`

**The derivative `(dr)/(d theta)` for` r = tan^2(3 - theta^3)` is ** `(dr)/(d theta) = -6*theta^2*tan(3 - theta^3)*sec^2(3 -...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

For` r = tan^2(3 - theta^3)` the derivative `(dr)/(d theta)` has to be determined. Use the chain rule.

`(dr)/(d theta)` = `2*tan(3 - theta^3)*sec^2(3 - theta^3)*(-3*theta^2)`

=> `-6*theta^2*tan(3 - theta^3)*sec^2(3 - theta^3)`

**The derivative `(dr)/(d theta)` for` r = tan^2(3 - theta^3)` is **`(dr)/(d theta) = -6*theta^2*tan(3 - theta^3)*sec^2(3 - theta^3)`